Znaleziska statków rzymskich rozbitych u wybrzeży południowej Galii od II w. p.n.e. do I w. n.e. jako świadectwa masowego handlu winem i oliwą - Góralczyk, Agnieszka (Studia Europaea Gnesnensia, 2015)
The article attempts to reconstruct the image of wine and oil trade in the western part of the Mediterranean. The analysis focuses on the wrecks of Roman vessels which sank at the coast of southern Gaul and the wine and oil amphorae carried in their holds.